PERSONAL BRANDING OF ISLAMIC PREACHERS IN DIGITAL DA'WAH: IMAGE, INTENTION, AND ADAB - Abdul Zuhri Pauzi; Abdul Hamid; Badrah Uyuni (QAULAN: Journal of Islamic Communication, 2026)
The development of digital media has transformed the way Islamic preachers preach, build relationships with audiences, and establish religious authority in the digital public sphere. This situation has prompted some religious preachers to develop personal branding as a communication strategy for preaching on social media, while also sparking debate about the relationship between image, intention, and the manners of preachers from an Islamic perspective. This study aims to analyze the transformation of the role of Islamic preachers through personal branding, using the preachers' images, intentions, and manners as an analytical framework. The study used a descriptive qualitative approach, with data collection methods including observation, in-depth interviews, and documentation of digital preaching activities. Data were analyzed using the Miles and Huberman model, focusing on data reduction, data presentation, and drawing conclusions. The results show that personal branding plays a significant role in shaping preachers' image and the audience's trust in digital preaching. However, personal branding can also shift the orientation of preaching towards popularity if not accompanied by sincere intentions. This study found that the balance between image, intention, and manners of preachers is an important factor in maintaining the integrity and quality of Islamic preaching in the digital space.